Fluoxetina: profilo terapeutico e farmacoeconomico di un prodotto generico - Della Pepa, Carlo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2003)
Fluoxetine has been the first antidepressive agent of the class of selective serotonine reuptake inhibitors (SSRI) to be introduced in therapy, back in 1987. The availability of SSRIs has meant a great advance in the treatment of major depression and other neuro-psychiatric pathologies. In this paper we review the scientific and clinical research on fluoxetine that has been published in the last six years, as the prior work has been extensively examined in a review conducted on the tenth anniversary of its introduction on the market. The review focuses on cost minimization strategies that can be conducted following the introduction of low cost generic fluoxetine.